Posttraumatic stress symptoms (PTSS) in patients with Cushing's disease before and after surgery: A prospective study. (August 2019) - Chen, Zhuang; Wang, Guoliang; Jiang, Che
Highlights: At preoperative stage, 30.6% CD patients developed PTSS who presented higher 24 h UFC and worse quality of life. There were still 33.3% of patients with preoperative PTSS persisted over a year after successful surgeries. After surgery, the mental health of CD patients showed consistent improvement. Compared with healthy individuals, CD patients in remission still performed worse in physical and mental health. Abstract: The aim of this study was to investigate the occurrence, correlated factors and prognosis of posttraumatic stress symptoms (PTSS) in patients with Cushing's disease (CD). A total of 49 patients who were newly diagnosed with CD and underwent transsphenoidal surgery in our hospital from April 2015 to August 2017 were asked to participate in this study. Another group of 49 age and sex matched healthy control participants were also included for comparison. PTSS (measured with Impact of Event Scale-Revised, IES-R), depression/anxiety (measured with Hospital Anxiety and Depression scale, HADS) and quality of life (QoL; measured with 36-item short-form, SF-36) were evaluated at pre-surgery, 6 months post-surgery and 12 months post-surgery. The results showed that at preoperative stage, 15 (30.6%) CD patients developed PTSS, and they had higher 24 h UFC, and presented worse levels of depression, anxiety and QoL compared with patients without PTSS. Although most of them recovered postoperatively, there were still 5/15 (33.3%) patients persisted with PTSS for over a year. Additionally, one patient with recurred CD developed PTSS between 6 and 12 months postoperatively. Among the whole group of CD patients, the PTSS severity showed consistent improvement after surgery, which was in accordance with the progressing trends of depression, anxiety and psychological aspects of SF-36. However, compared with healthy individuals, CD patients in remission still performed worse in physical/mental health. In conclusion, patients with CD can develop PTSS, and they may persist for over a year even after successful surgery. Combined psychological intervention is advised for these patients.